A facile yet versatile method for adsorption and relayed fluorescent detection of heavy metal ions. Issue 4 (August 2021) - Yang, Mingrui; Lin, Li; Wang, Bolin; Wang, Ying; Zhang, Li; Jiang, Yuanyuan; Zhao, Maojun; Zeng, Jun; Chen, Hui; Zhang, Yunsong
Abstract: The versatile treatment of heavy metal wastewater is serious challenge in practical application if an efficient, low-cost, stable and eco-friendly removal/detection method cannot be widely employed. Herein, we report a facile and effective methodology for adsorption and relayed fluorescent detection of heavy metal ions by substitution reaction effect of hydroxyapatite/Fe3 O4 (HAp/Fe3 O4 ) composite combined with Tetracycline Hydrochloride (TCH). The HAp/Fe3 O4 works as adsorbent for removal of heavy metal ions by substitution reaction, and the released Ca 2+ from HAp acts as indicator for relayed detection of adsorption efficiency. The maximum removal efficiencies of heavy metal ions (Pb 2+, Cd 2+, Cu 2+, Ni 2+, Zn 2+, Co 2+ ) by HAp/Fe3 O4 were over 96% in 100 mg/L. The low detection limitation (0.04 mg/L) and good linear relationship (0.1–100 mg/L) were obtained for Pb 2+, and other heavy metal ions display similar trends. The substitution reaction effect provides a promising pathway for removal and indirect measurement of wastewater with superb performance. Graphical Abstract: In HAp, the substitution reaction as a chemical adsorption process has excellent removal ability for heavy metals ions, and the released nontoxic Ca 2+ can work as indicator for relayed detection of adsorption efficiency. This discovery has enabled us to develop a valid and convenient approach to large-scale treatment/detection of heavy metal wastewater by the wise selection of appropriate adsorbents and fluorescent agent. ga1 Highlights: A facile method for adsorption and relayed fluorescent detection of heavy metal ions. Hydroxyapatite (HAp) highly adsorbed heavy metal ions through substitution reaction. An indirect method for measuring the amount of heavy metal ion adsorption. The fluorescent property of Ca-TC complex was used for quantitative determination. An σ-π feedback bond is proposed to explain the covalent connection.